Cultivating support during COVID‐19 through clinical supervision: A discussion article - Claire O'Donnell; Kathleen Markey; Louise Murphy; James Turner; Owen Doody (Wiley, 2023)
Abstract Aim This article aims to discuss how clinical supervision is an important approach in supporting frontline nurses and students during and post COVID‐19 through the lens of the nursing metaparadigms. Design Discussion article. Methods Discourse of the literature considering the importance of working collaboratively with healthcare and educational organisations in operationalising clinical supervision. Results The evidence base supporting clinical supervision as an effective support strategy for nurses exists, however, its implementation and practice has become sporadic. A resurgence is required to support student's and nurse's during this pandemic. It is timely for nurse educators to creatively engage with clinical partners in supporting clinical supervision to enhance both nurses and students pandemic practice experiences. Clinical supervision is proposed as one strategy to support and guide both nurses and students to develop, strengthen and challenge the effectiveness of their care during COVID‐19.